1985
DOI: 10.1042/bst0130053
|View full text |Cite
|
Sign up to set email alerts
|

Neurotensin degradation by soluble and membrane-associated enzymes from the brain

Abstract: The tridecapeptide NT (Glp1-Leu2-Tyr3-Glu4-Asn5-Lys6

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…As a result, it can be concluded that concomitant substitution at the Arg- (8) and Ile (12) positions with non-natural amino acids completely prevents peptidase degradation in rat serum. Prior studies have demonstrated the Arg(8)-Arg( 9) and the Tyr(11)-Ile (12) bond to be major sites of peptide cleavage in the brain; [45][46][47][48][49][50] hence, it is hypothesized that these peptides will be resistant to peptidases in the brain. Modifications of this method in order to quantify NT [8][9][10][11][12][13] and KK1-19 in brain homogenate are currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it can be concluded that concomitant substitution at the Arg- (8) and Ile (12) positions with non-natural amino acids completely prevents peptidase degradation in rat serum. Prior studies have demonstrated the Arg(8)-Arg( 9) and the Tyr(11)-Ile (12) bond to be major sites of peptide cleavage in the brain; [45][46][47][48][49][50] hence, it is hypothesized that these peptides will be resistant to peptidases in the brain. Modifications of this method in order to quantify NT [8][9][10][11][12][13] and KK1-19 in brain homogenate are currently under investigation.…”
Section: Discussionmentioning
confidence: 99%